Comparison of electromigration simulation in test structure and actual circuit - He, Feifei (2013)
With the rapid increase in circuit complexity, accurate reliability simulator is necessary as reliability testing for fabricated circuit is progressively more time and resource consuming. Simple 2D electromigration (EM) simulator has many limitations and most of the 3D EM simulations in the literature are using simple line-via structure which is only part of the real circuit structure. In this paper, a thorough comparison between simple 3D line-via structure model and 3D circuit model under different test conditions is performed using class-AB amplifier as an example, and the results showed that simple line-via structure simulation may not always correctly represent the real circuit failure site.